The Obligatory Law Applied to the Abram Conditions of Marriage of International Print - ‌Hassan, Prof. Dr. Mohamed أalal Hassan; Medhat, Lanya Kamal Medhat (Sulaimani Journal for Humanities, 2025)
Numerous disputes arise over the contract of marriage of an international nature, in particular with regard to the law applicable to the substantive and formal conditions for the validity of such marriage, as well as restrictions on the exclusion of competent foreign law and cases in which the competent foreign law is excluded from the provision of these conditions in response to public interest and public order requirements, or to avoid and prevent fraud towards the law s rights ", comparing Iraqi law with French and Kuwaiti law, regarding the adaptation of marriage requirements and the question of the distinction between such clauses, as such a distinction is of great importance in determining the rules of attribution governing the clause and thus determine the law applicable to its verification or failure. The Iraqi legislature did not provide, either in the Personal Status Law or in the Civil Code, a criterion by which a distinction could be drawn between formal and substantive conditions, nor did it specify the type of application of the competent law to the substantive requirements, since neither the inclusive application nor the distributed application had led to problems with the application of the spouses' law. Therefore, the legislator must establish a criterion for distinguishing between substantive and formal marriage requirements in order for the attribution rules to be properly applied, and the law applicable to these conditions is thus carefully defined.
Keywords: Subjective conditions of marriage; formal conditions of marriage; supporting regulations; foreign law; international marriage